欧普拉人生指南：生命中的快乐小事 - 欧普拉杂志 (The Editors of O, The Oprah Magazine) (人生顾问丛书;, 2018)
「实现别人的梦想，不可能快乐。 　　请活出自己的梦想， 　　如此方能确实领悟快乐的意义。」 　　“You can never be happy living someone else’s dream. 　　Live your own. And you will for sure know 　　the meaning of happiness.” 　　———— 欧普拉Oprah Winfrey